In vitro Capability of Multi-walled Carbon Nanotubes Modified with Gonadotrophin Releasing Hormone on Killing Cancer Cells - Bo-Zhang Yu; Jian-She Yang; Wen-Xin Li (Diagnostic and Treatment Advances in COVID-19 and SARS-CoV-2, 2023)
Oxidized and polished multi-walled carbon nanotubes (MWCNTs) were dispersed in aqueous solution, providing a highly stable suspension of purified, shortened, and functionalized carboxylic acid nanotubes. A gonadotrophin releasing hormone (GnRH), which was overexpressed in the plasma membrane of several types of cancer cells, was covalently anchored onto the surface of the oxidized MWCNTs via an amide linkage. The MWCNTs modified with GnRH (MWCNTs–GnRH) were characterized by UV–vis and emission spectra, and elemental analysis. Red-shift in the optical spectra consisting of the UV–vis absorption and emission spectra with the attraction of GnRH on the surface of the MWCNTs was observed due to the attraction of GnRH on the surface of the MWCNTs via \(π\) stacking, however, there was no property for a direct mixture of MWCNTs and GnRH, supporting the successful modification. Elemental analysis revealed that the sidewall coverage of MWCNTs by the GnRH was about 0.7% of the available surface area. The non toxic GnRH and MWCNTs can separately enter the DU 145 cells. In contrast, GnRH–MWCNTs entered the cells and showed toxicity in the malignant cells. These results showed that the newly formed toxic material had potential ability to kill the malignant cells with just a simple covalent bonding of the two.